Color of rhythm - a 3-d visual representation - Wang, L.; Guo, R.; Lu, P.; Tsai, P.-S. (International Journal of Sports Science and Engineering, 2010)
Rhythm is needed for all coordinated movements to be performed accurately and, without exception, sports skills are considered rhythmic in nature. Mature motor skill patterns have a definite stable rhythmic structure. Of all sensory systems, vision alone provides human beings with more than half of the information. Contrary to the fluidity of rhythm itself, static images, such as charts and figures have been used to illustrate the limited visual representations of rhythm. Present study explored the possibility of creating a 3-D visual representation of color-coded rhythm.